Association of ambulance response time and major adverse cardiac events in acute coronary syndrome - Shen, Jeremiah Ding Deck (2018)
Background: A common tenet in emergency medical service is that a faster response time equates to a better outcome in patients with acute coronary syndrome (ACS). We explored the association between ambulance response time (ART) and major adverse cardiac events (MACE) in patients diagnosed of ACS in Malaysia. Methods: This study was a retrospective cohort analysis conducted from 2014 until 2016 involving two emergency medical services (EMS) in Malaysia. Adult patients diagnosed with ACS and utilized the EMS to come to hospital were followed up to assess MACE within 30 and 90 days from the primary event. Multivariable logistic regression analysis was performed to evaluate the interaction between ART and MACE. Results: One hundred patients with an average age of 59.7 (SD=12.7) years old were included in the analysis. The average ART was 21.7 (SD=10.4) minutes. 29 patients developed MACE at 30 days and 40 patients developed MACE at 90 days post ACS. No significant association was found between ART and occurrence of MACE 30 and 90 days post ACS (OR= 0.99; 95% CI: 0.95, 1.03; P=0.679 and OR=0.98; 95% CI: 0.95, 1.02; P=0.446 respectively). Conclusion: ART was not significantly associated with MACE after both 30 and 90 days onset of ACS. This underscores the need for not driving ambulances with high speeds when responding to ACS cases.